SEED EXTRACT OF ABELMOSCHUS MOSCHATUS MEDIK REVERSES NAF-INDUCED BEHAVIORAL CHANGES THROUGH NEURODEGENERATION AND OXIDATIVE STRESS IN BRAIN OF RAT - Sudhakar, Kurmeti; Nageshwar, Mesram; Reddy K, Pratap (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study reports protective effect of Abelmoschus moschatus seed extract against sodium fluoride-induced neurodegeneration through oxidative stress, neurohistological, and behavioral observations in Wistar rats. Methods: A total of 20 Wistar rats (around 250 g) were randomly classified into four groups, namely, control, fluoride (NaF), fluoride + A. moschatus seed aqueous extract (AMAE), and fluoride + A. moschatus seed ethanol extract (AMEE). The control group animals received normal tap water, fluoride group received fluoridated water at the rate of 40 mg/kg b. wt., 3rd group rats treated with fluoride (40 mg/kg b. wt.) + AMAE (300 mg/kg b. wt.), and 4th group rats treated with fluoride (40 mg/kg b. wt.) + AMEE (300 mg/kg b. wt.). Neurobehavioral responses of rotarod, hot plate, and maze learning tests and oxidantive stress markers including lipid peroxidation (LPO), GSH levels, superoxide dismutase, CAT, and GSH peroxidase (GPx) activities, and also histology with H and E as well as congo red staining were studied in control, fluoride, and A. moschatus seed extract treated against fluoride groups. Results: Decreased neurobehavioral responses with rotarod, hot plate, and maze and enhanced LPO (p<0.05) levels were found in fluoride received animals. Whereas, the superoxide dismutase (SOD), CAT, GSH, and GPx were decreased (p<0.05) in NaF treatment. The rats received seed extract along with NaF showed significant reversal of behavioral and oxidative stress markers and the effect of ethanol extract was more pronounced than aqueous extract. The fluoride-treated group showed disturbed cell structure and reduced number of cells in H and E as well as congo red staining which was reversed in cell morphology and restored cell number in seed extract against NaF-treated group. As a result of increased LPO, decreased antioxidant system, and decreased number of cells, neurodegeneration was observed resulting in the disturbance in functions associated with reported behavior. Conclusion: Okra with high antioxidants activity, seed extract showed reversal of LPO levels and antioxidant status in the brain tissue. And also plant extract administered rats displayed normal cell structure and number of cells than only fluoride received group. Therefore, the aqueous and ethanolic extract of A. moschatus plant seeds has neuroprotective effects against fluoride-induced motor, nociceptive, learning behavior, and on histological structure of brain through antioxidant mechanism. The ethanol extract has shown more efficacy than aqueous extract.